Summary of the best evidence for nutritional support programs in nasopharyngeal carcinoma patients undergoing radiotherapy - Fan, Xiaomei; Cui, Huixia; Liu, Shasha (Frontiers in Nutrition, 2024)
Objective: To evaluate and summarize the best evidence for nutritional support in patients receiving radiotherapy for nasopharyngeal carcinoma and to offer guidance for clinical practice. Background: Patients with nasopharyngeal carcinoma undergoing radiotherapy often experience a high prevalence of malnutrition, and there is a lack of compiled guideline recommendations, which complicates the provision of a reference for clinical nursing. Methods: A systematic search of the literature revealed the best evidence of nutritional support for nasopharyngeal carcinoma patients undergoing radiotherapy. Included in the review were various types of literature, such as clinical guidelines, expert consensus, systematic evaluations, meta-analyses, evidence summaries, and original studies. The grading of evidence was conducted according to the Australian Joanna Briggs Institute Centre for Evidence-Based Health Care Evidence Pre-Grading System (2016 version). Data were gathered from a range of sources, including BMJ Best Practice, Scottish Intercollegiate Guidelines Network, Cochrane Library, Embase, PubMed, Web of Science, CINAL, CNKI, WanFang database, SinoMed, Yi Maitong Guidelines Network, Dingxiangyuan, Chinese Nutrition Society, European Society for Clinical Nutrition and Metabolism website, and American Society for Parenteral and Enteral Nutrition website. The search spanned from January 2013 to 2023. Results: A comprehensive review identified a total of 3207 articles, comprising 6 guidelines, 8 expert consensus articles, 4 systematic evaluations, 5 randomized controlled trials, 2 cohort trials, and 2 observational studies. From these articles, we synthesized 63 pieces of evidence, spanning 6 domains: nutritional risk screening and assessment, nutrient requirements, nutritional support, management of nutritional symptoms, functional exercise, and nutritional monitoring and follow-up. Conclusion: Sixty lines of evidence supporting nutritional support for nasopharyngeal carcinoma patients receiving radiotherapy were summarized. However, the evidence should be combined with the actual clinical situation, and it should be validated in the future by combining large-sample and multicenter studies to provide a more scientific and beneficial nutritional support program for nasopharyngeal carcinoma patients receiving radiotherapy.